STRATEGI KOMUNIKASI INOVATIF DALAM MEMPROMOSIKAN IDEOLOGI ISLAM BERKEMAJUAN: PENDEKATAN MUHAMMADIYAH - Ar Rafi, Khairi; Sumarlan, Iman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study explores the innovative communication strategies employed by Muhammadiyah in promoting the ideology of Progressive Islam through digital platforms. Utilizing the theoretical frameworks of Diffusion of Innovations (Rogers) and Communicative Constitution of Organizations (CCO), this research aims to examine how ideological messages are disseminated and adopted through digital communication channels. A qualitative approach was applied, involving in-depth interviews, direct observation, and document analysis of Muhammadiyah’s digital campaigns, including social media content and official publications. The findings reveal that the diffusion process follows a systematic progression, starting from knowledge exposure, persuasion, decision-making, implementation, to social confirmation. Muhammadiyah’s communication strategy integrates universal values such as education, social justice, and economic empowerment with engaging visual formats that appeal to digitally native youth. Inclusive narratives are delivered through infographics, videos, webinars, and action-based social programs, enhancing the relevance of the ideology in contemporary society. Furthermore, the involvement of charismatic figures, collaboration with educational institutions, and the use of Muhammadiyah’s organizational networks significantly accelerate the adoption of its messages. The study concludes that Muhammadiyah’s communication approach is adaptive, participatory, and context-sensitive, positioning it as a compelling model for ideological communication in the digital era. These findings contribute theoretically to the field of religious organizational communication and offer practical insights for developing technology-based da’wah strategies in the future.